Low‐Viscosity γ‐Butyrolactone‐Based Concentrated Electrolyte Solutions for LiNi0.5Mn1.5O4 Positive Electrodes in Lithium‐Ion Batteries. Issue 9 (19th June 2017) - Doi, Takayuki; Shimizu, Yusuke; Hashinokuchi, Michihiro; Inaba, Minoru
Abstract: Highly concentrated electrolyte solution with a low viscosity and high stability against oxidation was obtained by using a single solvent system of LiBF4 /γ‐butyrolactone (GBL). Although up to 4.65 mol kg −1 LiBF4 could be dissolved in GBL at room temperature, 3.87 mol kg −1 LiBF4 /GBL was a reasonable compromise to attain a low viscosity (52.1 mPa s) and a low GBL/Li molar ratio (3.00). Sodium carboxymethylcellulose and poly(acrylic acid) were used as binders for the spinel LiNi0.5 Mn1.5 O4 positive electrode and the graphite negative electrode, respectively, to suppress the swelling of conventional poly(vinylidene fluoride)‐based binder. The charge and discharge performances of the LiNi0.5 Mn1.5 O4 positive electrode and the graphite negative electrode were improved by using 3.87 mol kg −1 LiBF4 /GBL, as compared with concentrated propylene carbonate‐based electrolyte solution. Abstract : Putting on a performance : A highly concentrated electrolyte solution with a low viscosity and high stability against oxidation is obtained by using a single solvent system of LiBF4 /γ‐butyrolactone (GBL). The charge and discharge performances of the LiNi0.5 Mn1.5 O4 positive electrode and the graphite negative electrode are improved by using 3.87 mol kg −1 LiBF4 /GBL, as compared with concentrated propylene carbonate (PC)‐based electrolyte solution.